(untitled) (Bangladesh Journal of Pharmacology, 2016)
Current research analyzes the chemical composition of Ligustrum lucidum flower essential oil obtained by the hydrodistillation, and examines its anti-microbial mode of action against food-borne pathogenic bacteria. Gas chromatography-mass spectrometry analysis of the oil resulted in the determination of 44 different compounds, representing 85.2% of the total oil. The oil (1 mg/disc) showed significant antibacterial effect as diameters of inhibition zones (14.6 ± 0.2 19.7 ± 0.3 mm), as well as minimum inhibitory and minimum bactericidal concentrations values (2501000 and 2502000 µg/mL), respectively. Based on the susceptibility, L. lucidum flower oil revealed its mode of action on membrane integrity as confirmed by increased release of extracellular ATP (2.5 and 2.2 pg/mL), leakage of potassium ions (950 and 900 mM/L), loss of 260-nm absorbing materials (4.2 and 3.9 optical density), and increase in relative electrical conductivity (10.6 and 9.8%) against Staphylococcus aureus KCTC-1621 (Gram-positive) and Salmonella enterica ATCC-4731 (Gram-negative), respectively. Video Clip of Methodology: MIC determination: 10 min 32 sec Full Screen Alternate